Answer:
u = fv/(v - f)
Step-by-step explanation:
1/f = 1/u + 1/v
1/u = 1/f - 1/v = v/fv - f/fv = (v-f)/fv
1/u = (v-f)/fv
u = fv/(v - f)
Answer: x=1 or x=-3
Step-by-step explanation:
Quadratic formula is ![-b+-\sqrt{b^{2}-4ac } /2](https://tex.z-dn.net/?f=-b%2B-%5Csqrt%7Bb%5E%7B2%7D-4ac%20%7D%20%2F2)
a=1 b=2 c=-3
Substitute
![(-2+-\sqrt{2^{2}-4(1)(-3) }) /2\\(-2+-\sqrt{4+12}) /12\\(-2+-\sqrt{16}) /2\\(-2+-4) /2\\x=\frac{-2+4}{2} \\x=\frac{-2-4}{2} \\\\\\Simplify\\x=\frac{2}{2} \\\\x=\frac{-6}{2} \\\\Simplify\\x=1\\x=-3](https://tex.z-dn.net/?f=%28-2%2B-%5Csqrt%7B2%5E%7B2%7D-4%281%29%28-3%29%20%7D%29%20%2F2%5C%5C%28-2%2B-%5Csqrt%7B4%2B12%7D%29%20%2F12%5C%5C%28-2%2B-%5Csqrt%7B16%7D%29%20%2F2%5C%5C%28-2%2B-4%29%20%2F2%5C%5Cx%3D%5Cfrac%7B-2%2B4%7D%7B2%7D%20%5C%5Cx%3D%5Cfrac%7B-2-4%7D%7B2%7D%20%5C%5C%5C%5C%5C%5CSimplify%5C%5Cx%3D%5Cfrac%7B2%7D%7B2%7D%20%5C%5C%5C%5Cx%3D%5Cfrac%7B-6%7D%7B2%7D%20%5C%5C%5C%5CSimplify%5C%5Cx%3D1%5C%5Cx%3D-3)
Answer:
x=12
Step-by-step explanation:
Since this is a right triangle we can use the Pythagorean theorem
a^2 + b^2 = c^2 where a and b are the legs and c is the hypotenuse
9^2 + x^2 = 15^2
81 + x^2 = 225
Subtract 81 from each side
x^2 =225-81
x^2 =144
Take the square root of each side
sqrt(x^2) = sqrt(144)
x=12
Answer:
21 cups.
Step-by-step explanation:
6x3.5c=21c
C=cups
The answer will be -7
And if you want calculate it here’s this one 4-2-3-6